Catalytic Activity Towards Hydrogen Evolution Dependent of the Degree of Conjugation and Absorption of Six Organic Chromophores. Issue 4 (1st April 2020) - Aleksovska, Angela; Lönnecke, Peter; Addicoat, Matthew A.; Gläser, Roger; Hey‐Hawkins, Evamarie
Abstract: Conjugated materials can, in many cases, absorb visible light because of their delocalized π electron system. Such materials have been widely used as a photoactive layers in organic photovoltaic devices and as photosensitizers in dye‐sensitized solar cells. Additionally, these materials have been reported for applications in solar fuel production, working as photocatalysts for the hydrogen evolution reaction (HER). The synthesis of three flexible vinyl groups‐containing chromophores is reported. The catalytic activity towards hydrogen evolution of these chromophores has been investigated and compared to their non‐vinyl‐containing analogues. The catalytic effect was confirmed using two different approaches: electrochemical, using the chromophores to modify a working electrode, and photocatalytic, using the chromophores combined with platinum nanoparticles. A relationship between the degree of conjugation and the catalytic activity of the chromophores has been observed with the electrochemical method, while a relationship between the UV absorption in the solid state and the photocatalytic effect with platinum nanoparticles was observed. Abstract : The catalytic activity towards hydrogen evolution of three rigid and three flexible vinyl groups‐containing chromophores was confirmed by electrochemistry (electrode modified with chromophores) and photocatalysis (chromophores combined with platinum nanoparticles). A relationship between the degree of conjugation and the UV/Vis absorption and the catalytic activity has been observed.